(untitled) (The Journal of Medicine, Humanity and Media, 2024)
Newspapers and magazines, as the most important means of communication in modern China, are important media for disseminating scientific knowledge on health and epidemic prevention to the public. As a landmark publication of the Commercial Press, the "The Eastern Miscellany" faithfully recorded the historical changes of modern China from its inception in 1904 to its final publication in 1948. It is known as the "database of modern Chinese history" and has had a profound impact on the dissemination of medical and health knowledge, the establishment of social public health concepts, and the promotion of the construction of a national medical and health system in modern society. It has left abundant first-hand literature materials for research on the dissemination of modern Chinese health science knowledge and has extremely high academic value. The overall process of health and epidemic prevention policies and knowledge dissemination in "The Eastern Miscellany" presents four stages: the initial stage of publication (1904-1909), the development period (1909-1919), the mature period (1920-1941), and the declining period (1943-1948). In terms of dissemination content, the publication of health and epidemic prevention policies and scientific knowledge in "The Eastern Miscellany" is rich, mainly divided into two aspects: epidemic prevention and research, and public health construction, involving epidemic prevention laws and regulations, traffic quarantine, environmental health, rural health, health movements, and many other contents. Through the study of the dissemination of health and epidemic prevention scientific knowledge in the "The Eastern Miscellany", not only can we clarify the dissemination and development of health and epidemic prevention scientific knowledge in modern China from the perspective of mass media, but we can also see the important role and role played by newspapers and magazines in the dissemination of health and epidemic prevention scientific knowledge in modern China, and reflect the historical changes of modern Chinese medical society.